LAW EDUCATING WIFE AND CHILDREN PRIVATE VOCATIONAL SCHOOL OF PRESIDENT OF THE PROPHET OF MUHAMMAD SAW - Nurhadi Nurhadi (PAI RAFAH, 2019)
Islam as the most blessed religion of Allah swt (surah al-Imran verse 19), is also the proof of Islam's most perfect religion, perfected. Islam also regulates how the concept of education, both within the family and outside the family. This study aims to determine the hadith of the Prophet Muhammad PBUH relating to the responsibility and law of educating his wife and children in the household with religious education. This reason needs to be discussed, many in the community of husbands (parents) who neglect the obligations and responsibilities of educating family members, so that not a few households run aground in the middle of the road or at least broken home throughout life. This research is a literary model with primary sources of hadith book (al-tis'ah pole), and secondary data from the literature relating to this research. The result is that in the book of poles al-tis'ah according to the traditions of the Prophet Muhammad PBUH there are approximately 69 traditions related to the responsibility of educating his wife and children, of the 69 traditions, two traditions are discussed in detail (Tirmizi narration No. 2577 and Muslim No 2137, because these two traditions summarize the meaning of 67 other traditions, it can be concluded that educating wives and children for their husbands (fathers) the law is fardhu ain or obligatory for the head of the family as a form of responsibility to provide inner support (religious knowledge) to family members (wife and children) in the 69 traditions contain the command sentence "teach or educate", then in the method of jurisprudence "al-ashlu fil amri lil wujub" the meaning of the origin of each command is mandatory. "Therefore a wife or child has the right to sue her husband (father) to educate religion as an obligation in Islamic law.